Pengaruh Motivasi Intrinsik dan Motivasi Ekstrinsik Terhadap Peningkatan Produktivitas Kerja Karyawan Pada PT Automobil Jaya Mandiri Dealer Wuling Mlati Yogyakarta The Effect of Intrinsic Motivation And Extrinsic Motivation On Increasing Employee Product - Kasy, Joice Anggreini; Widiyanti, Anik (EBBANK, 2023)
PT Automobil Jaya Mandiri is an authorized dealer that serves Wuling car sellers. Wuling Motors Mlati Yogyakarta serves sales for the Yogyakarta, Klaten, Solo, Magelang, Purworejo and surrounding areas. In order to increase sales productivity, the role of HR is very important, for this reason, it is necessary to study the influence of work motivation on each employee both from within and from outside, so that work productivity can increase. The aim of this research is to find out whether intrinsic and extrinsic motivation have a significant effect on employee productivity either partially or simultaneously. In this study using quantitative data. Surveys, interviews and observations were used to collect data, and 33 employees of PT Automobil Jaya Mandiri were used as research samples. The SPSS 29.0 for Windows program is used to validate and verify data during data processing. The analytical method used is factor analysis and multiple linear regression analysis, hypothesis testing using F test analysis, and t test. Based on the results of the t (partial) test, it shows that there is a significant influence between intrinsic motivation and extrinsic motivation on employee work productivity (Y). Simultaneously the intrinsic motivation variable and the extrinsic motivation variable have a significant effect on employee work productivity (Y). This proves that the hypothesis Ho is rejected and Ha is accepted. This means that there is a significant effect of intrinsic motivation and extrinsic motivation on employee work productivity (Y).